The handbook for hay-making - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Hay and straw conservation. For small-scale farming and pastoral conditions FAO Plant Production and Protection Series, # 29, 2000. 318 pp. ISBN 9251044589 US$ 26 Euro 30.85